2019
DOI: 10.1155/2019/9691753
|View full text |Cite
|
Sign up to set email alerts
|

Nonemergent Percutaneous Coronary Intervention on an Unprotected Left Main Coronary Artery Supported with Impella® Heart Pump in Patients Ineligible for Surgical Revascularization

Abstract: Objectives. We sought to assess if ineligibility to coronary artery bypass grafting (CABG) constitutes a risk factor in patients who underwent a nonemergent unprotected left main coronary artery (ULMCA) percutaneous coronary intervention (PCI) with prophylactic Impella® heart pump support. Background. ULMCA PCI in patients not deemed eligible for CABG is associated with significantly worse outcomes compared to ULMCA PCI in eligible patients. Methods. Patients from the cVAD Registry and the PROTECT II trial who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…36,40 The most common complications of Impella support in elective clinical scenarios were access site bleeding and hemolysis. 44,47,50,52 To prevent the latter, frequent echocardiographic control of the Impella position is advisablethe teardrop should be about 3.5 cm from the aortic valve annulus to ensure that the inflow is in the midventricular cavity according to the manufacturer's recommendation.…”
Section: Complications Associated With Impella Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…36,40 The most common complications of Impella support in elective clinical scenarios were access site bleeding and hemolysis. 44,47,50,52 To prevent the latter, frequent echocardiographic control of the Impella position is advisablethe teardrop should be about 3.5 cm from the aortic valve annulus to ensure that the inflow is in the midventricular cavity according to the manufacturer's recommendation.…”
Section: Complications Associated With Impella Supportmentioning
confidence: 99%
“…The most common complications of Impella support in elective clinical scenarios were access site bleeding and hemolysis. 44,47,50,52 To prevent the latter, frequent echocardiographic control of the Impella position is advisable—the teardrop should be about 3.5 cm from the aortic valve annulus to ensure that the inflow is in the midventricular cavity according to the manufacturer’s recommendation. Acute renal failure and pericardial effusion were reported in patients with Impella support during VT ablation, whereas the reported incidence of cardiac tamponade ranged up to 11%, occurring mostly in patients undergoing epicardial mapping and catheter ablation.…”
Section: Complications Associated With Impella Supportmentioning
confidence: 99%
“…56 A recent RCT and postmarketing study suggested more complete revascularization and lower short-and intermediate-term rates of major adverse cardiac and cerebrovascular events with hemodynamic support with Impella than with an intra-aortic balloon pump. 57,58 An RCT is expected to begin enrollment in 2021 comparing Impella to no hemodynamic support in patients undergoing high-risk PCI. 59…”
Section: Other Indications For Percutaneous Coronary Intervention In Left Main Disease and Diabetes Mellitusmentioning
confidence: 99%
“…Since left main interventions seem particularly problematic in patients turned down for surgery, one may consider prophylactic hemodynamic support. One publication of 331 unprotected left main interventions noted similar mortality and morbidity between surgically eligible and ineligible patients who were treated with prophylactic impella support 4 …”
mentioning
confidence: 99%
“…One publication of 331 unprotected left main interventions noted similar mortality and morbidity between surgically eligible and ineligible patients who were treated with prophylactic impella support. 4 Most recently, the Outcomes of Surgically Ineligible Patients with Multivessel Coronary disease (OPTIMUM) Registry was reported but not yet published. 5 In this multicenter registry, 750 patients were turned down for surgery due to poor distal target/ conduit (19%), severe LV dysfunction/nonviable myocardium (17%), severe lung disease (10%), followed by frailty, advanced age and other factors.…”
mentioning
confidence: 99%